Surface distribution of Foraminifera in a New England salt marsh: Plum Island, Massachusetts - Jones, J.; Cameron, Barry (Atlantic Geology, 1987)
Salt marsh agglutinated foraminiferal assemblages, floristie zones and environmental subdivisions along the Plum Island barrier island system in Massachusetts resemble the zonation pattern for coastal marshes in the Maritime Provinces of Canada. Forty-three surface samples from high marsh, low marsh, tidal channel margin and elevated surface environments yielded seven species: Trochanmina macrescens, Tr. inflata, Miliammina fusca. Tiphotrocha comprimata. Amotium sal sum, Haplophragmoides bonplandi, and ArenopareUa mexicana. Analysis of the dead to living ratios does not show a significant preservational difference among the salt marsh environments. Analysis of the total distributions indicates significant differences among the foraminiferal assemblages as a function of surface environments. The high marsh is characterized by Trochanmina macrescens, Tiphotrocha comprimata and two of the lesa common species. The low marsh is characterized by Miliammina fusca, Trochanmina inflata, and Ammotium salsum. The tidal channel margin assemblage is similar to that of the low marsh except that Ammotium salsum is no longer significant. Although the elevated marsh surfaces contained no living specimens, a high marsh type assemblage of dead specimens was present. These cosmopolitan foraminiferal assemblages should be valid discriminators for the reconstruction of Holocene salt marsh paleoenvironments in many regions.